Determine the Frequency of Silent Cardiac Ischemia in Type II Diabetes Mellitus Patients - Tahira Sadiq, Zurqa Khalid, Fareha Kashan Theba, Kanwal Naz, Mujeebullah Tareen, Aniqa Saleem, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to ascertain the prevalence of silent cardiac ischemia in diabetic patients with type II diabetes. Study Design: Cross-sectional Place and Duration: This study was conducted at Fazaia Medical College, Islamabad from January, 2022 to June, 2022. Methods: Total 115 patients of type-II diabetes mellitus were presented in this study. After taking a thorough medical history, the patient had electrocardiography (ECG) both before and after exercise tolerance testing. This was done in addition to recording their height, blood pressure, weight, and fasting blood sugar levels (ETT). Changes in the electrocardiogram were analysed, and the patient was classified as having silent cardiac ischemia or not depending on the results of the ECG. SPSS 22.0 was used to analyze all data. Results: There were 75 (65.2%) males and 40 (34.8%) females in this study. The mean age was 51.13± 10.29 years and had mean BMI 26.7±8.44 kg/m2. Mean fasting blood sugar was 171±22 mg/dl. Frequency of hypertension was found in 47 (40.9%) cases and 38 (33.04%) patients were smokers. We found that 50 (43.5%) cases had silent cardia ischemia. There was a strong correlation between silent cardiac ischemia and factors such as increasing age, prolonged duration of diabetes mellitus, a smoking history, a history of hypertension, and an increased body mass index (p-value 0.05). Conclusion: We observed that silent cardiac is quite frequent in our population, which necessitates immediate measures to diagnose this issue early for the sake of improved results in the future. Keywords: Type II diabetes mellitus, BMI, Silent cardiac ischemia, Hypertension